(untitled) (The Journal of Psychology and Sociology, 2020)
The paper presents a pilot study for two phenomena, organizational commitment and career an- chors of university foreign language teachers. Career values were seen as predictors of organizational commitment. Internationalization and multilingualism of higher education entail the demand for foreign language teachers, who often teach, particularly, English in several workplaces. Knowing multi-dimen- sional connections between those phenomena makes it possible to influence organizational commit- ment through career orientations of teachers. Identifying and building organizational commitment is an issue of the university organizational culture and academic policy. The study objects are 66 university teachers for foreign languages from Almaty universities. The components of organizational loyalty and career orientations are the research subject matter. The study aimed at the organizational loyalty of university teachers and their career orientations as predictors. The research question focused on a relationship between organizational loyalty and career orientations of teachers. Conclusions reflect the results of the study. Key words: organizational commitment, loyalty, career anchors, university teacher.